IDENTIFIKASI KADAR SIANIDA PADA BIJI PICUNG MENTAH (Pangium edule Reinw) YANG BERASAL DARI CISEWU GARUT DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Dani Sujana (Jurnal Sains dan Teknologi Laboratorium Medik, 2020)
Pangi (Pangium edule Reinw.) or picung thrives in most of Southeast Asia, including Indonesia. Most of the people of Cisewu, Garut Regency, West Java consume picung seeds as food and as a complement to rice. Picung seeds contain cyanide, which has the potential to cause poisoning and even death if consumed in excess. In this study, cyanide analysis was carried out quantitatively using UV-Vis spectrophotometry and qualitatively using pictured paper. The results showed that 6 picung seeds from different trees were all positive for cyanide, indicated by the formation of a brick red color on picrat paper qualitatively, while the results of quantitative analysis of cyanide levels contained in picung seeds were 175 ppm.